Comparison of the utility of SARC-F, SARC-CalF, and calf circumference as screening tools for sarcopenia in patients with osteoporosis. - Yuki Ishihara; Toru Kusakabe; Akihiro Yasoda; Takuya Kitamura; Kazutaka Nanba; Mika Tsuiki; Noriko Satoh-Asahara; Tetsuya Tagami (PLoS ONE)
Aim Patients with osteoporosis who also have sarcopenia are at a high risk for falls and fractures. Early detection of sarcopenia is crucial for these patients. This study aimed to compare the effectiveness of SARC-F, SARC-CalF, and calf circumference (CC) as screening tools for sarcopenia in patients with osteoporosis. Methods This cross-sectional study was retrospectively conducted on patients who attended the outpatient clinic for Osteoporosis and Sarcopenia at Kyoto Medical Center. Sarcopenia was determined based on low skeletal muscle mass and weak handgrip strength. Sensitivity and specificity analyses were conducted on SARC-F, SARC-CalF, and CC. The diagnostic utility of these three tools was compared using the receiver-operating characteristic (ROC) curves and the area under the ROC curves (AUC). Results A total of 225 patients (men/women: 33/192) with a median age of 69.0 years (interquartile range: 61.0‒75.0) were enrolled. The prevalence of sarcopenia was found to be 11.6%. CC had the highest sensitivity (80.8%), while SARC-F had the highest specificity (93.0%) for detecting sarcopenia. ROC analysis revealed that all three tools had significant potential for sarcopenia diagnosis, with SARC-CalF having the highest AUC compared to SARC-F and CC (0.753 vs. 0.619 and 0.700). A multivariate logistic regression, incorporating other confounders as explanatory variables, revealed that SARC-CalF was independently related to sarcopenia (odds ratio: 14.80, 95% confidence interval: 3.83-57.30, p < 0.001). Conclusion In patients with osteoporosis, SARC-CalF is more effective in the early detection of sarcopenia than SARC-F and CC.